Prevalence of an Identity Crisis Within the Transgender Population of Pakistan - Zakir, Fahad; Inamulhaq; Sheikh, Humaira Babur (Annals of Human and Social Sciences, 2024)
This paper is an attempt to investigate the identity crisis, common to the transgender community of Pakistan. Pakistan’s transgender community has particular difficulties, such as discrimination and societal judgment as well as restricted access to assistance and medical services. The main objectives of the present research were to o look into the prevalence of identity crises are among transgender people in Pakistan and how they affect their mental health and general wellbeing Using data collected via surveys and interviews with transgender people in different parts of Pakistan, The data were subjected to a thematic analysis, with ten transgender persons aged 18 to 52 making up the focus group number. this study looks at the causes of identity crises in this community. In order to address the underlying causes of identity crises and foster endurance and well-being within the transgender population, it emphasizes the significance of community-based interventions, advocacy campaigns, and legislative changes. In this research was carried out by employing a qualitative research design via unstructured interviews. participation in the interview, 75 percentage of participants said that their rejection by others had no bearing on who they were. close friends in particular were very ready to ignore them, especially when it came to their own families.